Admissions : a memoir of surviving boarding school - James, Kendra (Grand Central Publishing, 2022)
"Kendra James began her professional life selling a lie. As an admissions officer specializing in diversity recruitment for select prep schools, her job was persuading students and families to embark on the same perilous journey, attending cutthroat and largely white schools similar to The Taft School, an elite institution in Connecticut where she had been the first African-American legacy student only a few years earlier. Forced to reflect on her own elite educational experience, she quickly became disillusioned by America's inequitable system. In ADMISSIONS, Kendra looks back at the three years she spent at Taft, from clashes with her lily-white roommate, to unlearning the respectability politics she'd been raised with, and a horrifying article in the student newspaper that accused Black and Latinx students of being responsible for segregation of campus. She contemplates the benefits of the education she got from Taft, which Kendra credits as playing a role in her career success, as well as the ways the school coddled her--perhaps, she now believes, too much. Through these stories, she deconstructs the lies and half-truths she herself would later tell as an admissions professional, in addition to the myths about boarding schools perpetuated by popular culture. With its combination of incisive social critique and uproarious depictions of elite nonsense, ADMISSIONS will resonate with anyone who has ever been The Only One in a room, dealt with racial microaggressions, or even just suffered from an extreme case of homesickness"--